The Influence of Earphone Usage Behaviour on Ear Disorders - Scempham Jarvey; Hertmaan Gouyaso (Newinera Publisher, 2021)
Is the use of earbuds linked to ear disorders? This research tries to find out. A proportional random sample method was used for the research. The main data and simple linear regression are used for descriptive statistics and statistical analysis of the findings. The habit of wearing earbuds has a negative impact on ear problems. Extended exposure to sound above 110 dB in loudness each day for more than 1 hour per day, along with extended earphone usage, may lead to impaired hearing. To minimize hearing loss, earphone use should be avoided if possible, and use should be limited to less than 1 hour a day, at lower volumes